Plasma endogenous endotoxin core antibody response to exercise in endurance athletes - Young, P.; Rauch, C.; Russo, I.; Gaskell, S.; Davidson, Z.; Costa, R. J. S. (International Journal of Sports Medicine, 2022)
The study aimed to investigate the impact of laboratory-controlled exertional and exertional-heat stress on concentrations of plasma endogenous endotoxin core antibody (EndoCAb). Forty-four (males n=26 and females n=18) endurance trained (VO2max 56.8min/kg/min) participants completed either: P1-2h high intensity interval running in 23°C ambient temperature (Tamb), P2-2h running at 60% VO2max in 35°C Tamb, or P3-3h running at 60% VO2max in 23°C Tamb. Blood samples were collected pre- and post-exercise to determine plasma IgM, IgA, and IgG concentrations. Overall resting pre-exercise levels for plasma Ig were 173MMU/ml, 37AMU/ml, and 79GMU/ml, respectively. Plasma IgM concentration did not substantially change pre- to post-exercise in all protocols, and the magnitude of pre- to post-exercise change for IgM was not different between protocols (p=0.135). Plasma IgA and IgG increased pre- to post-exercise in P2 only (p=0.017 and p=0.016, respectively), but remained within normative range (35-250MU/ml). P2 resulted in greater disturbances to plasma IgA (p=0.058) and IgG (p=0.037), compared with P1 and P3. No substantial differences in pre-exercise and exercise-associated change was observed for EndoCAb between biological sexes. Exertional and exertional-heat stress resulted in modest disturbances to systemic EndoCAb responses, suggesting EndoCAb biomarkers presents a low sensitivity response to controlled-laboratory experimental designs within exercise gastroenterology.